Streptococcus Intermedius Brain and Liver Abscesses After Dental Manipulation: a Case Report - Dib, Jony; Khalil, Majd; Chbib, Joyce; Hamdan, Manal (International Journal of Clinical Research, 2022)
Background: Brain abscesses are intracerebral infections with pus accumulation that can be fatal in most cases without appropriate treatment. The most common cause of brain abscesses are infections with streptococci and staphylococci. Streptococcus anginosus is a group of streptococci that are part of the normal flora of the oropharynx and are rarely the cause of severe bacterial infections. Case Report: Our patient is a 64-year-old man who underwent a dental procedure, and presented a few days later with a high-grade fever and decreased level of consciousness. He was found to have multiple brain abscesses and a liver abscess, and blood cultures revealed Streptococcus intermidius, which belongs to the Streptococcus anginosus group. The patient received appropriate treatment and recovered completely. Conclusion: Dental procedures, even simple tooth brushing, can cause bacteremia leading to multiple abscesses in different parts of the body, especially if a germ of the Streptococcus anginosus group has been detected in the blood culture.